2020
DOI: 10.1186/s12889-020-09303-2
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis outbreak in southern Ethiopia: challenges of detection, management, and response

Abstract: Background: Despite the availability of effective vaccines, pertussis remains endemic with high fatality rates in low and middle-income countries (LMIC). This study aims to describe an outbreak of pertussis in a health district of Ethiopia. The study highlights the challenges faced by the health system in identifying pertussis cases and appropriately responding to the outbreak at the district level. Methods: A descriptive cross-sectional study was conducted using data sourced from the District Public Health Em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Out of three deaths reported from pertussis outbreak, two have occurred among females with a case fatality rate of 0.91%. This result is in line with the report of a pertussis outbreak investigation in Mekdela district, Northwest Ethiopia [9], the Dara Malo district, Southern Ethiopia in 2018 [17], and the Janamora district, Amhara Regional State, Ethiopia in 2017 [18]. This nding indicates females are more affected than males which could be explained as females spend more time working at home and caring for children or adults, which puts them at higher risk of contracting the disease.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Out of three deaths reported from pertussis outbreak, two have occurred among females with a case fatality rate of 0.91%. This result is in line with the report of a pertussis outbreak investigation in Mekdela district, Northwest Ethiopia [9], the Dara Malo district, Southern Ethiopia in 2018 [17], and the Janamora district, Amhara Regional State, Ethiopia in 2017 [18]. This nding indicates females are more affected than males which could be explained as females spend more time working at home and caring for children or adults, which puts them at higher risk of contracting the disease.…”
Section: Discussionsupporting
confidence: 87%
“…Children aged below ve years are the most affected age group with an attack rate of 198/1000, which is in line with the ndings of a pertussis outbreak investigation in Mekdela district, Northwest Ethiopia [9], the Dara Malo district, Southern Ethiopia in 2018 [17], and with the study conducted in Aleppo [20]. The sex-speci c attack rate in this study indicates a high attack rate among females (57/1000) than males (54/1000).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The southern part of our country indicated that the overall attack rate was 1708 per100,000 population, and the fatality rate 3.3 per 1000 cases. This attack rate was very high in infant age groups and only 41% had completed the three-dose pertussis vaccine primary schedule, whereas the household survey resulted in 73% pentavalent vaccine coverage [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread implementation of pertussis vaccine immunisation, the incidence of this disease has decreased significantly 4 5. However, in the past two decades, outbreaks of pertussis have been reported in many areas worldwide,6–9 and large-scale outbreaks of pertussis (termed as ‘pertussis recurrence’) have also been reported in Shandong, Taiwan, and other regions in China 10 11…”
Section: Introductionmentioning
confidence: 99%